Rancang Bangun Sistem Informasi Promosi Pariwisata Kecamatan Lepar Pongok Kabupaten Bangka Selatan - Zuhri, Zuhri; Josi, Ahmat; Andriyanto, Sidhiq (Jurnal Inovasi Teknologi Terapan, 2023)
Lepar Pongok District has 8 tourist attractions but what can be displayed on the website are 6 tourist attractions, information about tourist attractions in Lepar Pongok District is still lacking, due to the lack of information about tourism in Lepar Pongok District, so with this the author is interested in making "Design of a Tourism Promotion Information System in Lepar Pongok District, South Bangka Regency". The aim of this final project is to design and build a Tourism Promotion Information System for Lepar Pongok District, South Bangka Regency as an effort to promote tourism in Lepar Pongok District. In the tourism promotion information system research in the Lepar Pongok sub-district, the data collection method used was the interview, documentation, observation, and literature study. And the method used in designing a tourism promotion information system website in Lepar Pongok district, the district is the waterfall method. The results of research on the tourism promotion information system website in the Lepar Pongok sub-district, district based on the tests that have been carried out, get a percentage value of 83% so this application is feasible to use. The conclusion from research on the tourism promotion information system website in Lepar Pongok sub-district, South Bangka district is that this website can make it easier for potential tourists to find out which tourism destinations are in Lepar Pongok sub-district and are feasible to use.